A methodological evaluation of the published consensus statements, recommendations and guidelines about surgical management in the course of coronavirus disease pandemic. (June 2021) - Bertolaccini, Luca; Iacono, Giorgio Lo; Mazzella, Antonio; Prisciandaro, Elena; Sedda, Giulia; Spaggiari, Lorenzo
Background: A project to benchmark the consensus statements, guidelines, and recommendations on surgical management in the course of the COVID-19 pandemic was developed to assess the methodology used. Standard and practical approaches for COVID-19 management in surgical patients to date are not accessible, despite the magnitude of the pandemic. A plethora of consensus statements, guidelines, and recommendations on surgical management in the course of COVID-19 epidemic have been rapidly published in the last three months. Methods: Each manuscript was scored on a seven-point scale in the different items and domains with the Appraisal of Guidelines for Research and Evaluation II. Results: Nine guidelines that met the inclusion criteria were assessed. Transnational cooperation produced only one guideline. Multivariable analysis showed that improved scores of stakeholders' involvement were related to internationally developed guidelines. Clarity of presentation was related to the contribution of scientific societies due to greater rigor of development. The rigor of development produced guidelines with a high overall value. Higher healthcare expenses did not produce superior guidelines. Conclusions: Evaluated by the Appraisal of Guidelines for Research and Evaluation II, the methodological characteristic of consensus statements, guidelines, and recommendations on surgical management during COVID-19 pandemic was relatively low. International development should be recommended as a model for the development of best methodological quality guidelines.